2007
DOI: 10.4067/s0365-28072007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance in Recombinant Chromosome Substitution Lines (RCSLs) Derived from the Cross Hordeum vulgare subsp. spontaneum (Caesarea 26-24) × Hordeum. vulgare subsp. vulgare cv. Harrington

Abstract: R E S U M E NSe estudió el rendimiento de grano (GY) y la tolerancia a la sequía de líneas recombinantes con substitución de cromosomas (RCSLs), provenientes de la cruza entre Hordeum vulgare L. subsp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…citroides PIs into watermelon cultivars. These populations should exhibit normal segregation ratios for a large number of markers, as was suggested in genetic improvement studies of barley [24]. These advanced recombinant populations can be useful for genetic mapping and the identification of chromosomal segments that were introgressed from the genome of a C. lanatus var.…”
Section: Introductionmentioning
confidence: 99%
“…citroides PIs into watermelon cultivars. These populations should exhibit normal segregation ratios for a large number of markers, as was suggested in genetic improvement studies of barley [24]. These advanced recombinant populations can be useful for genetic mapping and the identification of chromosomal segments that were introgressed from the genome of a C. lanatus var.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study was designed to identify quantitative traits, we were able to characterise and genetically dissect adaptive traits associated with the wild barley donor that had not been reported in previous studies of the RCSLs [ 9 , 35 37 , 51 ]. One such trait, which requires detailed observations, is spike glossiness.…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, we used the Recombinant Chromosome Substitution Lines (RCSLs) developed by Matus et al [ 9 ]. This was one of the first AB-populations developed using barley as a model crop and several studies have shown the potential of the lines for exploring novel allelic combinations for malting traits as well as for drought resistance and agronomic traits [ 9 , 35 37 ]. Considering these previous studies, our main goal was to effectively decipher the genetics underlying the variation for qualitative and quantitative traits using a minimum group of lines representing the genome of the exotic wild barley accession, Caesarea 26–24, in the genetic background of the elite North American spring malting barley, cv.…”
Section: Introductionmentioning
confidence: 99%
“…H. vulgare subsp. spontaneum has been used widely by plant breeders for its soil salinity tolerance (Shavrukov et al ., 2010), drought tolerance (Inostroza et al ., 2013) as well as other traits (Vincent et al ., 2013). Oat ( Avena sativa L.) has 29 CWR with A. byzantina K. Kock, A. fatua L., A. hybrida Peterm., A. occidentalis Durieu, A. sterilis L., A. trichophylla K. Koch in the primary genepool and the remaining taxa in the secondary and tertiary genepools (Vincent et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%